A Review on the Management of Small Renal Masses: Active Surveillance Versus Surgery - Marra, Giancarlo; Oderda, Marco; Allasia, Marco; Munegato, Stefania; Joniau, Steven; Gontero, Paolo (Anti-Cancer Agents in Medicinal Chemistry, 2018)
Despite the rise of small renal tumour (SRMs) diagnosis and related surgeries, death rate of kidney cancer is increasing, suggesting a non-optimal management of SRMs. Active Surveillance (AS) for kidney cancer was introduced to deal with this paradox. However, incertitude remains on whether and when AS can replace surgery in selected patients. We performed a literature search, reviewed and discussed the evidence in favour of AS or surgery for SRMs. Histopathology and natural history of SRMs, including the percentage of benign tumours amongst SRMs, tumour growth rate, life expectancy of SRMs patients being generally older, and current results of AS series seem to support its use in selected groups. However, kidney cancer is a heterogeneous entity, metastasis and ≥T3a status can be found also for SRMs and no biomarkers or other parameters are available to identify lethal SRMs. Despite the recent improvement in the diagnostic and prognostic work through imaging modalities, renal biopsies and nomograms, the interpretation of a survival plot subjectively is still not possible. The majority of AS studies are retrospective and extensive level 1 evidence cohorts with long term follow up are lacking. No unanimity is present regarding inclusion and exclusion criteria to undergo AS, follow up timings and AS exit criteria. Surgery is the only definitive treatment and remains the current standard. A better understanding of kidney cancer biology and SRMs behaviour is needed to clarify the role of AS and its indications.
Keywords: management